2008
DOI: 10.1063/1.2902970
|View full text |Cite
|
Sign up to set email alerts
|

A sodium atom in a large water cluster: Electron delocalization and infrared spectra

Abstract: Ab initio molecular dynamics simulations modeling low-energy collisions of a sodium atom with a cluster with more than 30 water molecules are presented. We follow the dynamics of the atom-cluster interaction and the delocalization of the valence electron of sodium together with the changes in the electron binding energy. This electron tends to be shared by the nascent sodium cation and the water cluster. IR spectra of the sodium-water cluster are both computationally and experimentally obtained, with a good ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 48 publications
2
30
0
3
Order By: Relevance
“…4a), OH bond breaking occurs and products like NaOH, Na 2 O and H 2 are produced. Electron solvation has been suggested to be the ratedetermining step, and products such as NaOH cannot exist stably without repeated collisions between Na and water clusters Cwiklik et al, 2008a;Mundy et al, 2000;Vorontsov and Novakovskaya, 2009). Near the NP surface (Fig.…”
Section: Effect On Swr Of Change In Physical Properties At the Liquidmentioning
confidence: 97%
“…4a), OH bond breaking occurs and products like NaOH, Na 2 O and H 2 are produced. Electron solvation has been suggested to be the ratedetermining step, and products such as NaOH cannot exist stably without repeated collisions between Na and water clusters Cwiklik et al, 2008a;Mundy et al, 2000;Vorontsov and Novakovskaya, 2009). Near the NP surface (Fig.…”
Section: Effect On Swr Of Change In Physical Properties At the Liquidmentioning
confidence: 97%
“…The barrier was reduced to $8 kcal/mol, since the hydrated electron moved to the outershell with increasing size. On the other hand, Cwiklik et al carried out on-the-fly MD simulations, and found that the cluster was unreactive due to the low collisional energy with more than 30 water molecules [19]. They also observed the recombination of H and OH in the trajectories of Na(H 2 O) 4,5 with the initial condition corresponding to the transition state determined by Liu et al The recombination occurred even during the reactive trajectory in the vibrationally-excited Na(H 2 O) 34 [20].…”
Section: Introductionmentioning
confidence: 97%
“…The interest sodium-doped water clusters (Na(H 2 O) n )) [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] and anion water clusters ((H 2 O) n -) [16][17][18][19][20][21][22] have attracted is attributed to their role as prototype systems for clarifying the mechanism of the emergence of the hydrated electron [23,24]. The dynamics of electronically excited states of the hydrated electron has received special attention in the context of electron initiated chemical processes and radiation damage of biological matter [7,[9][10][11]19,[25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%